Brain Metastases of Non–Small Cell Lung Cancer: Prognostic Factors in Patients with Surgical Resection - Antuña, Aida Ramos; Vega, Marco Alvarez; Sanchez, Carmen Rodriguez; Fernandez, Vanesa Martin (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background and Study Aims Bronchogenic carcinoma is the cancer that most commonly metastasizes to the brain. The standard treatment schedule for these patients is still unclear, although recommendation level 1 class I advocates for surgical resection together with postoperative whole-brain radiotherapy for patients with good Karnofsky performance status (KPS). We performed a study to identify prognostic factors for the long-term survival of patients with brain metastases from non–small cell lung cancer (NSCLC).Patients This retrospective single-center study included 71 patients with brain metastases from NSCLC having undergone surgical metastasectomy between January 2002 and January 2015.Results The average age was 58.8 years. A total of 85.9% of the lesions were located in the supratentorial region, 61.9% of the lesions were < 3 cm, and 80.3% of cases were solitary brain metastases. Complete resection was achieved in 90.1% of patients. Clinical debut with motor involvement was associated with higher rates of incomplete surgical resection. Patients with motor deficits had a worse preoperative KPS. The preoperative KPS was > 70 in 74.6% of patients, and the postoperative KPS was > 70 in 85.9% of patients. Overall, 84.5% of the brain surgeries had no complications. Brain metastases were diagnosed as a synchronous presentation in 64.7% of patients.The average survival after brain surgery was 20.38 months. The survival rate was 66.2% at 6 months, 45.1% at 12 months, 22.5% at 24 months, 14.1% at 36 months, and 8.5% at 48 months. Patients < 55 years of age showed a higher survival rate at 12 months and 48 months. Patients > 70 years of age showed a higher mortality rate at 6 months. Complete surgical brain metastasis resection was associated with an increased survival at 6 months, and patients undergoing primary lung surgery had better survival rates at 48 months. A preoperative KPS > 70% improved the prognosis of patients at 6 and 24 months. Surgical complications reduced survival at 6 and 12 months.Conclusion Surgical resection may be beneficial for a given group of patients: a preoperative KPS > 70; age < 55 years, complete surgical brain metastasis resection, no surgical complications, patients with primary lung surgery, and complete radiotherapy treatment. We did not find any significant difference regarding further factors that probably affect survival rates such as size or number of metastases.
Keywords: non–small cell lung cancer; brain metastases; prognostic factors; surgical resection